The Change in Customers’ Purchasing Power during the COVID-19 Pandemic Era - Rosa, Fenny; Rosyid, Syahron Al; Daniman, Iman; Saputra, Supriatna Toni; Ramadhan, Raden Dicky (Interdisciplinary Social Studies, 2022)
The COVID-19 pandemic has made many changes that have occurred very quickly, making consumers change their behavior in determining the purchase of goods and services. The purpose of this study is to provide general information or representation about changes in consumer behavior, especially on the purchasing power of consumers during the COVID-19 pandemic  in order to meet their living needs. This study uses a literature study in which the researcher collects a number of books and magazines related to the problem and purpose of the study. Researchers also analyzed data available on internet portals regarding e-commerce transactions in Indonesia. The results showed that consumer purchasing power in the indicators of selecting types of goods and services through E-Commerce during the COVID-19 pandemic  was dominated by almost 50% by the food industry, the second is the personal need for hygienic such as masks, hand sanitizers, etc.  This change in purchasing power is illustrated by the increase in transactions in e-commerce during the COVID-19 pandemic.